IL-6 Upregulates Protein S Expression in the HepG-2 Hepatoma Cells - Hooper, W Craig; Phillips, Donald J; Ribeiro, Maria; Benson, Jane; Evatt, Bruce L (Thrombosis and Haemostasis, 1995)
Several pro-inflammatory cytokines have been shown to be important in the modulation of the procoagulant response. However, what role these cytokines may have in the regulation of coagulation inhibitors is poorly understood. While the hepatocyte is a primary site of synthesis for the anticoagulant proteins C and S, it is also a major target cell for the proinflammatory cytokine, IL-6. We have found that stimulation of HepG-2 hepatoma cells with IL-6 (5 ng/ml) significantly increased the production of the anticoagulant cofactor, protein S, in both a time and dose dependent fashion. This increase was seen at both the RNA and protein level. A mouse monoclonal neutralizing antibody to human IL-6 suppressed the IL-6 effect in a concentration dependent fashion. IL-6 also increased the release of the C4b-binding protein but had no effect on protein C production. When combined with either dexamethasone or soluble IL-6 receptor, the IL-6 response was significantly enhanced. Oncostatin M, a functionally related cytokine, had a similar effect while other related cytokines, IL-11 and leukemia inhibitory factor, only had a marginal effect. IL-1, TGF-β, and TNF-α had no significant effect on protein S production. These results indicate that IL-6 may play an important regulatory role in the anticoagulant pathway.